In-depth meta-analysis: unilateral PKP demonstrates significant advantages in treating osteoporotic vertebral compression fractures—an expanded RCT study with GRADE scoring - Xiao, Lin; Li, Wei; Yan, Jingxin; Luo, Lei; Li, Ting (Frontiers in Surgery, 2025)
BackgroundPercutaneous kyphoplasty (PKP) has become a mainstream intervention for osteoporotic vertebral compression fractures (OVCFs). While existing systematic reviews comparing unilateral and bilateral PKP approaches provide preliminary insights, they are limited by methodological inconsistencies and inconclusive evidence regarding comparative efficacy.MethodsWe conducted a comprehensive systematic review of randomized controlled trials (RCTs) up to July 2024, searching major English databases (Cochrane Library, Embase, PubMed, Scopus, Web of Science) and Chinese databases (CNKI, VIP, and Wanfang).ResultsThe pooled analysis of 35 RCTs (N = 3,362) revealed no statistically significant differences between unilateral and bilateral PKP in long-term outcomes, including visual analog scale scores (P = 0.62), Oswestry Disability Index scores (P = 0.77), and Cobb angle correction (P = 0.64). However, unilateral PKP demonstrated significant perioperative advantages: shorter operative time (P < 0.00001), a lower dose of bone cement injection (P < 0.00001), and a reduced radiation dose (P < 0.00001). Furthermore, the study also found that unilateral PKP had a lower rate of bone cement leakage (P < 0.0001) and a reduced overall complication rate (P < 0.0001) compared to bilateral PKP.ConclusionUnilateral PKP offers advantages over bilateral PKP, including shorter operation time, lower polymethylmethacrylate injection dose, reduced radiation exposure, lower bone cement leakage, and fewer complications. Therefore, unilateral PKP may be a preferable option for patients with OVCF, providing similar clinical outcomes with reduced procedural risks and resource requirements.